Diversity Literacy: Transforming Pesantren Education from Doctrinal Memorization to an Interpretive Approach - Niza Baits Fadlilatuzzahro; Mambaul Ngadhimah (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This research is motivated by the dominant paradigm of religious learning in Islamic boarding schools (pesantren) which still emphasizes memorization, so that space for interpretation, critical reflection, and dialogue regarding the reality of diversity has not developed optimally. This condition has the potential to limit the strengthening of religious moderation in multicultural Indonesian society. This study aims to analyze the transformation of diversity literacy in Islamic boarding schools from a doctrinal memorization pattern to an interpretive approach through a synthesis of Robert Jackson's thoughts and Azyumardi Azra's Islamic pluralism. The study used a qualitative approach with a library research type. Data were obtained from various literature on Islamic boarding school education, religious moderation, multicultural education, yellow book learning, and bahtsul masa'il activities, then analyzed using content analysis techniques. The results of the study indicate that diversity literacy in Islamic boarding schools has shifted from memorization-oriented learning to a more dialogical, reflective, and contextual process. In addition, Azyumardi Azra's concept of Islamic pluralism is relevant in strengthening religious moderation through the values of wasathiyah, tolerance, and ukhuwah basyariyah. The integration of interpretive approaches and Islamic pluralism also contributes to the development of multicultural education in Islamic boarding schools by encouraging openness, respect for differences, and a culture of deliberation through discussions of religious texts and bahtsul masa'il (Islamic discourse). These findings underscore the potential of Islamic boarding schools to develop students who are religious, moderate, and adaptable to a diverse society.